1981
DOI: 10.1103/physreva.23.2978
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of blackbody radiation with xenon Rydberg atoms

Abstract: Effects due to the interaction of 300 K background radiation with Xe(nfj Rydberg atoms are reported. Transitions to nearby d and g levels are observed, When the ambient photon density is reduced to that appropriate to liquidnitrogen temperature by cooling the apparatus, a corresponding reduction in the transition rates to these levels is observed, The transition rates are found to be consistent with those predicted by use of quantum-defect theory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In the 1980-s, the interaction of Rydberg atoms with blackbody radiation was studied in various contexts. The attention was mainly focused on calculations and measurements of lifetimes of Rydberg states [3][4][5][6][7][8] and BBR-induced Stark shifts [2,9]. However, only a few studies considered ionization of Rydberg atoms by BBR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the 1980-s, the interaction of Rydberg atoms with blackbody radiation was studied in various contexts. The attention was mainly focused on calculations and measurements of lifetimes of Rydberg states [3][4][5][6][7][8] and BBR-induced Stark shifts [2,9]. However, only a few studies considered ionization of Rydberg atoms by BBR.…”
Section: Introductionmentioning
confidence: 99%
“…Curves (1), (4), and (7) are the direct BBR-induced photoionization rates at the ambient temperatures of T =77, 300, and 600 K, respectively. Curves (2),(5), and (8) are the total BBR-induced ionization rates at the amplitude of extraction electric field pulses of E=5 V/cm for ambient temperatures of T =77, 300, and 600 K, respectively. Curves (3),(6), and (9) are the total BBR-induced ionization rates at the amplitude of extraction electric-field pulses of E=10 V/cm for ambient temperatures of T =77, 300, and 600 K respectively.…”
mentioning
confidence: 99%
“…It has also been shown that at the ambient temperature of 300 K BBR can photoionize Rydberg atoms with n ∼ 20 at astonishingly high rates (∼ 10 3 s −1 ) [2,3,4]. Strong effect of BBR on Rydberg atoms is related to large matrix elements of bound-bound and bound-free transitions between Rydberg states in the microwave and far infrared spectral range [5].…”
mentioning
confidence: 99%
“…The blackbody radiation hypothesis was not as daring as it might seem. This mechanism had been extensively investigated (Hildebrandt et al, ) for neutral noble gas atoms laser‐excited to specific Rydberg states that were then observed to transition to even higher states under essentially collision‐free conditions. The main objection to extension of this well‐documented phenomenon to our mass spectrometric experiments was the susceptibility of high Rydberg states to field ionization (in fact this property was used as the diagnostic technique in the neutral atom work).…”
Section: Hands Across the Ocean: Guelph‐swansea Collaborationmentioning
confidence: 99%